A Green Leap Forward? Eco-State Restructuring and the Tianjin–Binhai Eco-City Model. Issue 6 (2nd June 2016) - Chang, I-Chun Catherine; Leitner, Helga; Sheppard, Eric
Abstract : Chang I-C. C., Leitner H. and Sheppard E. A green leap forward? Eco-state restructuring and the Tianjin–Binhai eco-city model. Regional Studies . China has experienced a remarkable explosion of designated eco-cities since the year 2000, with Tianjin–Binhai becoming the best-practice model. Embedded in broader political economic changes, shifting multi-scalar regimes of environmental governance have shaped this efflorescence. Applying eco-state restructuring, this paper argues that eco-city construction became a new strategic project after the 2000s, driven by central state-driven model cities and assessment initiatives. This also led to a very different kind of 'best practice' eco-city model: Tianjin–Binhai, a China–Singapore collaboration in which greenness is manufactured rather than adapted. Notwithstanding significant implementation problems, Tianjin–Binhai's status as best practice persists, raising questions about what it means to claim eco-city status.